Non-CEO top managers' monitoring power and CEO pay-performance sensitivity in state-owned enterprises: Evidence from Chinese state-owned listed firms - Qianhua Lei; Rui Lu; Liuyang Ren (China Journal of Accounting Research, 2019)
Few studies have focused on the role of non-CEO top manager inside directors in corporate governance, especially in the context of emerging countries. Despite their tendency to be subject to CEOs, non-CEO top manager inside directors can counterbalance CEOs in specific situations. Using panel data on state-owned listed companies in China, we conduct an empirical study of how non-CEO top manager inside directors influence CEO pay-performance sensitivity under serious agency conflicts. We find that the proportion of non-CEO top manager inside directors is significantly negatively correlated with CEO pay-performance sensitivity in state-owned enterprises, whereas the shareholding proportion of the controlling shareholders weakens this relationship. Furthermore, we find that non-CEO top manager inside directors significantly increase executives' on-the-job consumption. Our conclusions are robust to endogeneity testing and alternative specifications. Few studies have focused on the role of non-CEO top manager inside directors in corporate governance, especially in the context of emerging countries. Despite their tendency to be subject to CEOs, non-CEO top manager inside directors can counterbalance CEOs in specific situations. Using panel data on state-owned listed companies in China, we conduct an empirical study of how non-CEO top manager inside directors influence CEO pay-performance sensitivity under serious agency conflicts. We find that the proportion of non-CEO top manager inside directors is significantly negatively correlated with CEO pay-performance sensitivity in state-owned enterprises, whereas the shareholding proportion of the controlling shareholders weakens this relationship. Furthermore, we find that non-CEO top manager inside directors significantly increase executives' on-the-job consumption. Our conclusions are robust to endogeneity testing and alternative specifications.
Keywords: 650; Inside directors; State-owned enterprises; Non-CEO top managers; Pay-performance sensitivity